How and why to educate to old age? - geragog perspective - Anna Leszczyńska-Rejchert (Jan Dlugosz University, 2022)
Due to the progressive aging process of modern societies, the issue of preparation for old age has become extremely important. In terms of representatives of geragogy (pedagogy of old age), the most important form of preparation for old age is education for old age. The article reviews the concept of Polish educators in the field of "learning old age", and also formulates a proposal for gerontological education, covering all age groups.